KONSTRUKSI LELAKI DALAM CHICKLIT “THE HOPELESS ROMANTIC’S HANDBOOK” DAN “CINTAPUCINNO” - Mega Subekti; Trisna Gumilar (Balai Bahasa Kalimantan Tengah, 2017)
In popular literature, chicklit is one of the genres that focuses on the women's issues. For some scholars chicklit has a simple formula. In cultural studies, chicklit enriches various discourses especially the discourse of feminism.In this paper, analyzed about the construction of men in